Quality achieving excellence (London : Taylor Made Film, 1992)
The video shows how to go about implementing TQM in an organisation
Part I. Lampeter & Son (22 min.) - Part II. Case studies ; featuring Texaco, Cala Homes, ICL (47 min.)
Keywords: Total quality management